2018
DOI: 10.3390/en11081957
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Temperature Evaluation of a High-Temperature Insulation System for Liquid-Immersed Transformer

Abstract: Abstract:A high-temperature oil-paper insulation system offers an opportunity to improve the overloading capability of distribution transformers facing seasonal load variation. A high-temperature electrical insulation system (EIS) was chosen due to thermal calculation based on a typical loading curve on the China Southern Power Grid. In order to evaluate candidate high-temperature insulation systems, Nomex ® T910 (aramid-enhanced cellulose) immersed in FR3 (natural ester) was investigated by a dual-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…Thermal properties are improved by reducing the thermal conductivity of the unit's liquid and solid dielectrics. The two most common types of solid dielectrics (paper insulation) for liquid immersed transformers are TUK and variations of Dupont's Nomex (910 or 410), which are documented as having at least 10 • C better thermal performance than the former [46][47][48][49].…”
Section: New Unit Design Changes-normal Operationsmentioning
confidence: 99%
“…Thermal properties are improved by reducing the thermal conductivity of the unit's liquid and solid dielectrics. The two most common types of solid dielectrics (paper insulation) for liquid immersed transformers are TUK and variations of Dupont's Nomex (910 or 410), which are documented as having at least 10 • C better thermal performance than the former [46][47][48][49].…”
Section: New Unit Design Changes-normal Operationsmentioning
confidence: 99%
“…Based on the study, it was reported that the intensity of the discharge processes, comparing the same voltage levels, was mostly higher when streamers developed in ester liquids. Zhang et al [9] studied the performance of new alternative insulating oil/paper systems based on ester/Nomex, respectively, for high temperature applications, based on a typical loading curve on the China Southern Power Grid. Authors evaluated the physiochemical and mechanical properties along with the thermal index of the oil paper insulation system and reported that the considered new oil/paper insulation system is a promising one for high thermal applications compared to mineral oil/kraft paper insulation systems.…”
Section: A Review Of the Special Issuementioning
confidence: 99%
“…The moisture due to aging mechanism leads to reduced dielectric strength and increased viscosity especially for the aged oil. Hence, the electrical properties deteriorate; the breakdown voltage and the resistivity decrease, and the dielectric dissipation factor increase as reported by several researchers [13][14][15][16][17]. The degree of polymerization (DP) and tensile strength (TS) of paper are reduced and these precipitate the deterioration of the solid insulation.…”
Section: Introductionmentioning
confidence: 97%